Extracorporeal shock wave therapy for isokinetic muscle strength around the knee joint in athletes with patellar tendinopathy - Cheng, L.; Chang, S.; Qian, L.; Wang, Y.; Yang, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to explore the efficacy of 16 weeks of extracorporeal shockwave therapy in athletes with patellar tendinopathy. METHODS: Athletes with patellar tendinopathy were matched for age, height and body weight and assigned to the experimental group (N.=26) or control group (N.=25). Subjects in the experimental group received 16 rounds (once per week) of extracorporeal shockwave therapy (2000 single shocks; strength, 1.5 to 3.0 bar; shock frequency, 9 to 12 Hz). Subjects in the control group received physical treatments, such as acupuncture, ultrasonic wave, and microwave therapy. RESULTS: After 16 weeks, Visual Analog Scale (VAS) Score in the experimental group was reduced by 69.4% (P<0.01) compared with that at 0 weeks. Knee joint 60°/s and 240°/s peak torques were increased by 17.2% (P<0.01) and 7.2% (P<0.05), respectively, and extensor endurance by 17.4% (P<0.05). VAS Score in the control group was reduced by 16.9% (P<0.01) at 16 weeks compared with 0 weeks, and the knee joint 60°/s peak torque was increased by 8.2% (P<0.05). For between-groups comparisons, the VAS Score in the experimental group was reduced by 62.7% (P<0.01); whereas knee joint 60°/s and 240°/s peak torques increased by 8.8% and 5.8%, respectively, and extensor endurance by 12.5% (P<0.05). There were no significant differences between male and female subjects (P>0.05). CONCLUSIONS: Extracorporeal shock wave therapy has a positive effect on patellar tendinopathy in athletes, with no gender differences in therapeutic effect. Extracorporeal shock wave therapy may be used to alleviate pain and improve knee joint extensor strength and endurance.